2009 International Conference on Parallel Processing Workshops 2009
DOI: 10.1109/icppw.2009.33
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Messages Delivery Time on Vehicular Delay-Tolerant Networks

Abstract: Abstract-Vehicular Delay-Tolerant Networks (VDTNs) are an application of the Delay-Tolerant Network (DTN) concept, where the movement of vehicles and their message relaying service is used to enable network connectivity under unreliable conditions. To address the problem of intermittent connectivity, long-term message storage is combined with routing schemes that replicate messages at transfer opportunities. However, these strategies can be inefficient in terms of network resource usage. Therefore, efficient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…This contribution extends the main features of a previous laboratory testbed [13,[16][17][18] applying them into a real deployment (an embedded VDTN testbed). Simulations [19] and real experiments [20] contribute for modeling and analysis of vehicular architectures.…”
Section: Introductionmentioning
confidence: 77%
“…This contribution extends the main features of a previous laboratory testbed [13,[16][17][18] applying them into a real deployment (an embedded VDTN testbed). Simulations [19] and real experiments [20] contribute for modeling and analysis of vehicular architectures.…”
Section: Introductionmentioning
confidence: 77%
“…Our previous research efforts on the effect of scheduling and drop policies in the performance of vehicular delay-tolerant networks have shown that scheduling bundles with longer remaining lifetimes to be sent first, results in decreasing the bundles average delay significantly and increasing the overall bundles delivery ratio [12,16]. Based on those results, in each of the above-described buffer management strategies, bundles are sorted based on their remaining lifetimes per each priority class.…”
Section: Scheduling Policiesmentioning
confidence: 99%
“…Such a cooperative data delivery scheme would be useful for many applications such as vehicular sensor networking, traffic safety, vehicular telematics, and infotainment applications. A few works in the literature proposed cooperative communications models with relay-based mechanisms in DTNs and mobile ad hoc networks to decrease the delay of data delivery (e.g., [2], [3], [4]). The key assumption in all of the existing schemes is that the mobile nodes which are located near each other always help each other for data delivery.…”
Section: Introductionmentioning
confidence: 99%